2007
DOI: 10.1128/jb.00555-07
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Evokes a Metabolic Adaptation That Favors Increased NADPH Synthesis and Decreased NADH Production in Pseudomonas fluorescens

Abstract: The fate of all aerobic organisms is dependent on the varying intracellular concentrations of NADH and NADPH. The former is the primary ingredient that fuels ATP production via oxidative phosphorylation, while the latter helps maintain the reductive environment necessary for this process and other cellular activities. In this study we demonstrate a metabolic network promoting NADPH production and limiting NADH synthesis as a consequence of an oxidative insult. The activity and expression of glucose-6-phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
158
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(172 citation statements)
references
References 42 publications
14
158
0
Order By: Relevance
“…2A). The level of NADH in PQ-treated WT cells dropped markedly; a similar observation has been made after antibiotic treatment (29). Our data suggested that WT cells experienced increased oxidative stress when treated with PQ, whereas mutants did not.…”
Section: Physiological and Phenotypic Alterations In The Absence Of Thesupporting
confidence: 70%
See 1 more Smart Citation
“…2A). The level of NADH in PQ-treated WT cells dropped markedly; a similar observation has been made after antibiotic treatment (29). Our data suggested that WT cells experienced increased oxidative stress when treated with PQ, whereas mutants did not.…”
Section: Physiological and Phenotypic Alterations In The Absence Of Thesupporting
confidence: 70%
“…The NADH/NAD ϩ ratio under PQ conditions was lower in the WT, likely due to the fact that the glyoxylate shunt bypasses two NADH-generating steps. Cells show an increased NADH/NAD ϩ ratio when NADH oxidation is slowed by limitation of electron acceptors (29). The addition of PQ did not alter the NADH/NAD ϩ ratio in the aceA mutants, indicating that respiration in these cells was maintained, perhaps through a combination of pathways; lower oxygen consumption and higher denitrification-related events were observed (Fig.…”
Section: Physiological and Phenotypic Alterations In The Absence Of Thementioning
confidence: 92%
“…Second, H 2 O 2 could impact different metabolic pathways which are interconnected, including glutathione metabolism, glycolysis, the TCA cycle, and the DNA repair system. The functioning of the enzymes in these pathways and also the activity of the ATP synthase are dependent on the redox potential of the cells (NAD + /NADH, NADP + /NADPH ratios), and as a consequence the ATP concentration is regulated by this redox potential (Haddock and Jones, 1977;Singh et al, 2007;Oka et al, 2012). If for instance NAD + is depleted when the repair system is activated to avoid potential DNA damages induced by H 2 O 2 , then ATP is depleted, and finally all the metabolic pathways involving these compounds are impacted and a complete change in the metabolome can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Several ROS-scavenging systems such as glutathione reductase (GR), as well as ascorbate require NADPH to reduce and regenerate their oxidized active sites whereas others such as catalase utilize NADPH in order to avoid the formation of intermediates which hinder the ability of the enzyme to function (Kirkman and Gaetani, 2006;Singh et al, 2007). Since NADPH is a key component of the anti-oxidative defense mechanisms of cells, NADPH-generating enzymes are highly active under oxidative stress.…”
Section: Nadph/nadh Ratiomentioning
confidence: 99%